2021
DOI: 10.3390/cells10040825
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Kindlins and the Control of Integrin Function

Abstract: Integrins serve as conduits for the transmission of information between cells and their extracellular environment. Signaling across integrins is bidirectional, transducing both inside-out and outside-signaling. Integrin activation, a transition from a low affinity/avidity state to a high affinity/avidity state for cognate ligands, is an outcome of inside-signaling. Such activation is particularly important for the recognition of soluble ligands by blood cells but also influences cell-cell and cell-matrix inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Phosphorylation is another important aspect of kindlin functionality, which has been validated experimentally at T8 and T30 position for kindlin1; Y193, S159, S181, and S666 for kindlin2; T482 and S484 for kindlin3 29 . Computational predictions indicate a complete loss of T8 and S484 mutation sites in kindlin1 and kindlin3, respectively.…”
Section: Mutations Affects Structure-function Dynamics Of Kindlinsmentioning
confidence: 85%
“…Phosphorylation is another important aspect of kindlin functionality, which has been validated experimentally at T8 and T30 position for kindlin1; Y193, S159, S181, and S666 for kindlin2; T482 and S484 for kindlin3 29 . Computational predictions indicate a complete loss of T8 and S484 mutation sites in kindlin1 and kindlin3, respectively.…”
Section: Mutations Affects Structure-function Dynamics Of Kindlinsmentioning
confidence: 85%
“…Previous studies have demonstrated that Talin and Kindlin are indispensable mechanosensitive adaptor proteins in integrin activation. However, details about how Talin and Kindlin synergistically activate integrin were not fully understood. ,, It might be a rational hypothesis that Kindlin assisted Talin in activating integrin via transmitting mechanosignals. We herein studied the effect of tension on the interaction of the β1 integrin cytoplasmic tail with the Talin-F3 domain by performing “ramp-clamp SMD simulations” with different tensile forces.…”
Section: Discussionmentioning
confidence: 99%
“…The 14-3-3ζ proteins are dimers and could bind both phosphorylated T/S residues in integrin β-chains and phosphorylated kindlin-3. Kindlin-3 is phosphorylated at several sites, but the double-mutant T482/S484-AA in kindlin-3 inhibited adhesion of T lymphocytes, which shows that phosphorylation of kindlin-3 is functionally important [ 37 , 73 ].…”
Section: The Interactions Of Cytoplasmic Proteins With Integrins Are Regulated By Integrin Phosphorylationmentioning
confidence: 99%